Systematic Literature Review Etnomatematika: Pendidikan Matematika pada Kearifan Lokal Sasak - Wardani, Iwan Usma; Suarni, Ni Ketut; Margunayasa, I Gede (LP. Ma'arif Janggan Magetan, 2023)
The aim of this research is to find out mathematical concepts related to the ethnomathematics of local wisdom of Sasak culture. This research is a Systematic Literature Review (SLR) which was carried out by identifying, reviewing, evaluating and interpreting all available research. The design used in this research is to summarize, review and analyze 9 articles with the scope of discussing the Ethnomathematics of Sasak Culture with details of one article published in the reputable journal Q2 and the rest in the accredited National Journal Sinta. Searches for these articles were carried out through online journals such as journal articles from Google Scholar, Research Gate, SINTA, DOAJ, and Scopus. The conclusion of this research is the finding of mathematical concepts related to Ethnomathematics, local wisdom of Sasak Culture, consisting of Flat Plane Geometry, Geometric Space Structures, Geometric Transformation Concepts, Measurement, Volume of Rotating Objects, Perimeter and Area of Flat Plane Structures.